2018
DOI: 10.3390/met8100803
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nd Electrodeposition from the Aprotic Organic Solvent Dimethyl Sulfoxide

Abstract: The use of organic solvents in an electrolytic system for neodymium electrorecovery by electrolysis at low temperatures is studied in the current work. More specifically, an alternative route, that of the system of DMSO (Dimethyl sulfoxide) with dissolved NdCl3 has been researched and has given promising results. The study of this electrolytic system has been divided into two stages. Firstly, the characteristics of the electrolyte, the dissolution of NdCl3 in DMSO, the conductivity and the viscosity of NdCl3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Song et al demonstrated Ni-P-ZrO 2 -CeO 2 composite coatings on #45 steel using the jet-electrodeposition technique and achieved an optimal coating condition (e.g., potential and current density) for improving surface properties, hardness, and wear resistance [16]. Bourbos et al studied the recovery of neodymium (Nd) by galvanostatic electrolysis at −0.8 µA and potentiostatic electrolysis at −2 V in dimethyl sulfoxide with dissolved 0.1 M NdCl 3 , where the best result was obtained by pulsed electrolysis at low temperatures under stirring [17]. Li et al prepared a Ni-Mo-La composite using electro-codeposition in a weak alkaline solution of Ni and Mo ions mixed with La 3+ ion [18].…”
Section: Introductionmentioning
confidence: 99%
“…Song et al demonstrated Ni-P-ZrO 2 -CeO 2 composite coatings on #45 steel using the jet-electrodeposition technique and achieved an optimal coating condition (e.g., potential and current density) for improving surface properties, hardness, and wear resistance [16]. Bourbos et al studied the recovery of neodymium (Nd) by galvanostatic electrolysis at −0.8 µA and potentiostatic electrolysis at −2 V in dimethyl sulfoxide with dissolved 0.1 M NdCl 3 , where the best result was obtained by pulsed electrolysis at low temperatures under stirring [17]. Li et al prepared a Ni-Mo-La composite using electro-codeposition in a weak alkaline solution of Ni and Mo ions mixed with La 3+ ion [18].…”
Section: Introductionmentioning
confidence: 99%
“…The potential suitability of organic solvents such as dimethyl sulfoxide (DMSO) was studied using NdCl 3 salt, where different electrolysis parameters including electrolysis mode, supporting electrolyte, Nd 3+ concentration, temperature and stirring were analysed to understand their impact on Nd electrodeposition [51]. The application of a pulsed current or voltage was concluded to be favourable compared to traditional galvanostatic or potentiostatic polarisation as this resulted in increased mass deposited (3 vs. 12 mg) and higher purity of the Nd metal electrodeposit.…”
Section: Recovery Of Nd Via Electrodepositionmentioning
confidence: 99%
“…Recovery of these elements and thus securing of supply of raw materials independently of non-European market is still the focus of research today. Four papers deal with the recovery of REE [8][9][10][11].…”
Section: Contributionsmentioning
confidence: 99%